Aplikasi Remote Sensing dan Geographics Information System untuk Menunjang Database LP2B dan Agrowisata di Subak Sembung Kecamatan Denpasar Utara - IMAS CAHYANINGTIYAS; INDAYATI LANYA; NI MADE TRIGUNASIH (Agrotrop : Journal on Agriculture Science, 2021)
The Application of Remote Sensing and Geographics Information System for database SLA and Agrotourism in Subak Sembung, North Denpasar District. The Regional Spatial Plan (SP) of Denpasar City has designated Subak Sembung as an Agroecotourism Area. Subak Sembung is highly recommended as Sustainable Food Agriculture (SFAL). The determination of the SFAL area requires a geospatial-based agricultural land resource database. The goal is to compile a remote sensing-based SFAL database and Geographical Information System (GIS). Methods of visual analysis of satellite images, field surveys, thematic mapping, and land ownership as well as evaluation of existing agro-ecotourism conditions, especially Sapta Pesona. The conclusion of this study: the Subak Sembung resource potential database (land resources ( LR), artificial resources ( AR), Agricultural Resources, (AgR), Human Resources (HR) and land ownership) is classified as good, equipped with a geospatial-based thematic map of wetland ownership, worthy of being designated as SFAL. Owner farmers 57.24%, cultivators 42.76%. The average age of farmers is 52 years, with elementary school education. The potential of agro-tourism destinations is good, there are two entrances to the jogging tract from the main road, industry, promotion and institutions that still need to be improved to increase the attractiveness of agro-tourism.